Cancer negatively impacts on sexual function in adolescents and young adults: The AYA HOPE study - Wettergren, Lena; Kent, Erin E.; Mitchell, Sandra A.; Zebrack, Brad; Lynch, Charles F.; Rubenstein, Mara B.; Keegan, Theresa H. M.; Wu, Xiao‐Cheng; Parsons, Helen M.; Smith, Ashley Wilder (Psycho-oncology (Chichester, England), 2017)
Objective This cohort study examined the impact of cancer on sexual function and intimate relationships in adolescents and young adults (AYAs). We also explored factors predicting an increased likelihood that cancer had negatively affected these outcomes. Methods Participants (n = 465, ages 15–39) in the Adolescent and Young Adult Health Outcomes and Patient Experience (AYA HOPE) study completed two surveys approximately 1 and 2 years post‐cancer diagnosis. We used multivariable logistic regression to determine factors negatively affected by perceptions of sexual function at 2 years post‐diagnosis. Results Forty‐nine percent of AYAs reported negative effects on sexual function at 1 year post‐cancer diagnosis and 70% of those persisted in their negative perceptions 2 years after diagnosis. Those reporting a negative impact at 2 years were more likely to be 25 years or older (OR, 2.53; 95% CI, 1.44–4.42), currently not raising children (OR, 1.81; 95% CI, 1.06–3.08), experiencing fatigue (OR, 0.99; 95% CI, 0.975–0.998) and more likely to report that their diagnosis has had a negative effect on physical appearance (OR, 3.08; 95% CI, 1.97–4.81). Clinical factors and mental health were not significant predictors of negative effects on sexual function. Conclusions Many AYAs diagnosed with cancer experience a persistent negative impact on sexual life up to 2 years following diagnosis. The findings underscore the need to develop routine protocols to assess sexual function in AYAs with cancer and to provide comprehensive management in the clinical setting. Copyright © 2016 John Wiley & Sons, Ltd.